Consuming and producing linked open data: the case of OpenCourseWare. Issue 1 (2014) - Nelson Piedra; Edmundo Tovar; Ricardo Colomo‐Palacios; Jorge Lopez‐Vargas; Janneth Alexandra Chicaiza
<x xml:space="preserve"> Abstract </x> Purpose – The aim of this paper is to present an initiative to apply the principles of Linked Data to enhance the search and discovery of OpenCourseWare (OCW) contents created and shared by the universities. Design/methodology/approach – This paper is a case study of how linked data technologies can be applied for the enhancement of open learning contents. Findings – Results presented under the umbrella of OCW‐Universia consortium, as the integration and access to content from different repositories OCW and the development of a query method to access these data, reveal that linked data would offer a solution to filter and select semantically those open educational contents, and automatically are linked to the linked open data cloud. Originality/value – The new OCW‐Universia integration with linked data adds new features to the initial framework including improved query mechanisms and interoperability. <ack> <x xml:space="preserve"> Acknowledgements </x> This work has been partially funded by Madrid Regional Government through the project eMadrid (Ref:S2009/TIC‐1650) "Research and Development for e‐learning technologies", Project AL12‐PID‐09 (UPM) Universidad Politécnica de Madrid, Universidad Técnica Particular de Loja and scholarship provided by the "Secretaría Nacional de Educación Superior, Ciencia y Tecnología" of Ecuador (SENESCYT). The authors thank OCW Consortium, OCW‐Universia and technical personnel of TAWSBC on UTPL. </ack>